Sectoral labour reallocation: An agent-based model of structural change and growth - Francisco Adilson Gabardo; Gabriel Porcile; Jo\~ao Basilio Pereima Neto (EconomiA, 2020)
The shift of labour out of the agricultural sector and into the manufacturing and services sectors seems to be an important factor in explaining why some countries are so much richer than others. Therefore, understanding not only the driving mechanisms and forces behind the process of structural change but also how these mechanisms interact and reinforce each other becomes crucial. In the present work, we develop an agent-based model (ABM) where structural change is driven by income and relative prices effect. The income effect is generated by the assumption of a simple non-homothetic hierarchical demand structure where consumers spend their wealth following a particular priority ordering. The relative prices effect results from different sectoral productivity growth rates. The model is capable of theoretically replicating the dynamics of structural change where labour is reallocated across the three macro-sectors of agriculture, manufacturing and services. We have calibrated the model's parameters, so that the artificial employment share trajectories would match those of Sweden for the period of 1890-2010. The results suggest that, the income and relative prices effect are complementary in generating a process of structural change of the type experienced by developed economies. If some assumptions regarding agents' behaviour and sectoral relative conditions are respected, the model shows that it possible to theoretically yield structural changes in an agent-based model focusing only on first principles such as tastes and technologies.
Keywords: O00; O41; L16; 330; Agent-based model; Growth; Income effect; Relative-price effect; Structural change